Sequence organization and evolutionary dynamics of Brachypodium-specific centromere retrotransposons - Qi, L. L.; Wu, J. J.; Friebe, Bernd R.; Qian, C.; Gu, Y. Q.; Fu, D. L.; Gill, Bikram S. (My University, 2013)
Brachypodium distachyon is a wild annual grass belonging to the Pooideae, more closely related to wheat, barley, and forage grasses than rice and maize. As an experimental model, the completed genome sequence of B. distachyon provides a unique opportunity to study centromere evolution during the speciation of grasses. Centromeric satellite sequences have been identified in B. distachyon, but little is known about centromeric retrotransposons in this species. In the present study, bacterial artificial chromosome (BAC)-fluorescence in situ hybridization was conducted in maize, rice, barley, wheat, and rye using B. distachyon (Bd) centromere-specific BAC clones. Eight Bd centromeric BAC clones gave no detectable fluorescence in situ hybridization (FISH) signals on the chromosomes of rice and maize, and three of them also did not yield any FISH signals in barley, wheat, and rye. In addition, four of five Triticeae centromeric BAC clones did not hybridize to the B. distachyon centromeres, implying certain unique features of Brachypodium centromeres. Analysis of Brachypodium centromeric BAC sequences identified a long terminal repeat (LTR)-centromere retrotransposon of B. distachyon (CRBd1). This element was found in high copy number accounting for 1.6 % of the B. distachyon genome, and is enriched in Brachypodium centromeric regions. CRBd1 accumulated in active centromeres, but was lost from inactive ones. The LTR of CRBd1 appears to be specific to B. distachyon centromeres. These results reveal different evolutionary events of this retrotransposon family across grass species.
Citation: Qi, L., . . . Gill, B. (2013). Sequence organization and evolutionary dynamics of Brachypodium-specific centromere retrotransposons. Chromosome Research, 21, 507-521. https://doi.org/10.1007/s10577-013-9378-4
Keywords: Brachypodium distachyon; Centromere retrotransposons; Evolution